Microalgal Metallothioneins and Phytochelatins and Their Potential Use in Bioremediation - Balzano, Sergio; Sardo, Angela; Blasio, Martina; Chahine, Tamara Bou; Dell’Anno, Filippo; Sansone, Clementina; Brunet, Christophe (Frontiers in Microbiology, 2020)
The persistence of heavy metals (HMs) in the environment causes adverse effects to all 23 living organisms; HMs accumulate along the food chain affecting different levels of biological 24 organisations, from cells to tissues. HMs enter cells through transporter proteins and can bind 25 to enzymes and nucleic acids interfering with their functioning. Strategies used by microalgae 26 to minimise HM toxicity include the biosynthesis of metal-binding peptides that chelate metal 27 cations inhibiting their activity. Metal-binding peptides include genetically encoded 28 metallothioneins (MTs) and enzymatically produced phytochelatins (PCs). A number of 29 techniques, including genetic engineering, focus on increasing the biosynthesis of MTs and 30 PCs in microalgae. The present review reports the current knowledge on microalgal MTs and 31 PCs, describes the state of art of their use for HM bioremediation and other putative 32 biotechnological applications, also emphasising on techniques aimed at increasing the cellular 33 concentrations of MTs and PCs. In spite of the broad metabolic and chemical diversity of 34 microalgae, that are currently receiving increasing attention by biotechnological research, 35 knowledge on MTs and PCs from these organisms is still limited to date.